Faster recovery and bowel movement after early oral feeding compared to late oral feeding after upper GI tumor resections: a meta-analysis - Sindler, Dóra Lili; Mátrai, Péter; Szakó, Lajos; Berki, Dávid; Berke, Gergő; Csontos, Armand; Papp, Csenge; Hegyi, Péter; Papp, András (Frontiers in Surgery, 2023)
Background: Upper GI tumors are among the five most common malignancies, counting more than 1 600 000 occurrences worldwide. After a successful resection in these cases, the role of early oral feeding (EOF) was questionable, due to the possibility of fatal anastomosis leakage. It is still debated whether EOF is more advantageous compared to late oral feeding. Our study aimed to compare the effect of early postoperative oral feeding and late oral feeding after upper gastrointestinal resections due to malignancy. Methods: Two authors performed an extensive search and selection of articles independently to identify randomized control trials (RCT) of the question of interest. Statistical analyses were performed including mean difference, odds ratio with 95% confidence intervals, statistical heterogeneity, and statistical publication bias, to identify potential significant differences. The Risk of Bias and the quality of evidence were estimated. Results: We identified 6 relevant RCTs, which included 703 patients. The appearance of the first gas (MD=-1.16; p=0.009), first defecation (MD=-0.91; p<0.001), and the length of hospitalization (MD=-1.92; p=0.008) favored the EOF group. Numerous binary outcomes were defined, but significant difference was not verified in the case of anastomosis insufficiency (p=0.98), pneumonia (p=0.88), wound infection (p=0.48), bleeding (p=0.52), rehospitalization (p=0.23), rehospitalization to the intensive care unit (ICU) (p=0.46), gastrointestinal paresis (p=0.66), ascites (p=0.45). Conclusion: Early postoperative oral feeding, compared to late oral feeding has no risk of mortality or the several possible postoperative morbidities after upper GI surgeries, but has several advantageous effects on a patient's recovery. Key words: early oral feeding, upper GI surgery, meta-analysis, upper GI cancer, ERAS